Analisis Kesuksesan Aplikasi Maxim di Kota Jambi Menggunakan Delone and Mclean - Fahry, Muhammad; Oktaria M, Randa; D, Gregorius; Borroek, Maria Rosario; Feranika, Ayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Maxim application is an online transportation service that is currently popular in the city of Jambi, not only with modern online transportation features but also many features that are useful for users in everyday life. The aim of this research is to analyze the level of success of the Maxim application in the city of Jambi using the Delone and Mclean method. Data was taken from 385 respondents distributed via Google form. The questionnaire was distributed online, then analyzed using the structural equation modeling (SEM) method and the SmartPLS 4.0 tool. The research results show that from 9 hypotheses there are 8 accepted hypotheses, including HI, H2, H3, H4, H5, H7, H8, H9 with an R Square value of 0.383 for the user satisfaction variable, 0.373 for the net benefit variable (Net Benefit), and 0.423 for the use variable (Use). So it can be concluded that the Maxim application has quite a positive or good influence because this model is stated to be in accordance with the substance in presenting results.